Transsacral-Transiliac Screw Stabilization: Effective for Recalcitrant Pain Due to Sacral Insufficiency Fracture. Issue 9 (September 2016) - Sanders, Drew; Fox, Joshua; Starr, Adam; Sathy, Ashoke; Chao, John
Abstract : Objectives: To evaluate the effectiveness of transsacral-transiliac screw fixation for the treatment of sacral insufficiency fractures that fail nonoperative treatment. Design: A pilot study series of consecutive patients identified over 5 years were treated and followed prospectively. Setting: Academic-affiliated, tertiary referral, level 1 trauma center in Dallas, TX. Patients/Participants: Patients were selected on the basis of presenting diagnosis, and failure of nonoperative treatment of their sacral insufficiency fracture. Eleven patients entered to the study, and 10 completed follow-up. Intervention: Placement of transsacral-transiliac screws for sacral insufficiency fracture. Main Outcome Measurements: Comparison of preoperative and postoperative Visual Analog Scale scores and Oswestry Low Back Disability Index scores. Results: Patients experienced statistically significant improvement in both outcome measures after intervention. No complications encountered. Conclusions: Transsacral-transiliac screw fixation seems to be a safe and effective treatment for sacral insufficiency fractures recalcitrant to nonoperative management. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.